2014
DOI: 10.1002/art.38713
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cartilage DNA Methylome in Knee and Hip Osteoarthritis

Abstract: ObjectiveThe aim of this study was to characterize the genome-wide DNA methylation profile of chondrocytes from knee and hip cartilage obtained from patients with osteoarthritis (OA) and hip cartilage obtained from patients with femoral neck fracture, providing the first comparison of DNA methylation between OA and non-OA hip cartilage, and between OA hip and OA knee cartilage.MethodsThe study was performed using the Illumina Infinium HumanMethylation450 BeadChip array, which allows the annotation of ∼480,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
197
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(212 citation statements)
references
References 40 publications
11
197
0
Order By: Relevance
“…In a comparison of hip cartilage from patients with OA and unaffected controls, 5,322 dif ferentially methylated loci were identified. 83 Interestingly, the hipOA samples clustered into two groups, with a total of 15,239 differentially methylated loci between them, including genes involved in inflammation and immu nity. 83 In another study, 1,214 differentially methylated genetic targets were identified in a comparison of paired samples of knee cartilage showing mild or severe OA.…”
Section: Inflammation In Oamentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparison of hip cartilage from patients with OA and unaffected controls, 5,322 dif ferentially methylated loci were identified. 83 Interestingly, the hipOA samples clustered into two groups, with a total of 15,239 differentially methylated loci between them, including genes involved in inflammation and immu nity. 83 In another study, 1,214 differentially methylated genetic targets were identified in a comparison of paired samples of knee cartilage showing mild or severe OA.…”
Section: Inflammation In Oamentioning
confidence: 99%
“…83 Interestingly, the hipOA samples clustered into two groups, with a total of 15,239 differentially methylated loci between them, including genes involved in inflammation and immu nity. 83 In another study, 1,214 differentially methylated genetic targets were identified in a comparison of paired samples of knee cartilage showing mild or severe OA. 84 A number of the identified genes were related to devel opmental and celldifferentiation pathways, supporting the proposed involvement of these mechanisms in OA.…”
Section: Inflammation In Oamentioning
confidence: 99%
“…DNMT1, however, is largely responsible for maintaining the DNA methylation signatures created by these de novo enzymes during cell division. Recent genome-wide methylation profiling studies have identified differentially methylated loci in the genome of human OA chondrocytes, thereby suggesting the involvement of DNMT-driven mechanisms in the development and/or progression of OA (18,(22)(23)(24)(25)(26). This study was designed to address the potential role of the de novo Dnmt3 enzymes in regulating murine articular cartilage homeostasis.…”
Section: -Methylcytosine (5mc)mentioning
confidence: 99%
“…mRNA was reverse-transcribed in a Progene thermocycler (Techne, Staffordshire, UK) using a high-capacity cDNA reverse transcription kit (4368814; Applied Biosystems) following the manufacturer's instructions. qRT-PCR was performed on three pellet replicates (from each patient) to determine gene expression relative to two reference genes, according to published guidelines (Bustin et al, 2009): hypoxanthine-guanine phosphoribosyltransferase-1 (HPRT1 human; RT00059066) (Foldager et al, 2009;Rushton et al, 2014) and TATA box-binding protein (TBP; QT00000721) (Foldager et al, 2009;PomboSuarez et al, 2008) were selected based on low coefficiencies of variance across both supplement types (data not shown). Several genes (Table 1) were chosen to determine the chondrogenic phenotype after redifferentiation.…”
Section: Total Collagen Content In the Pelletsmentioning
confidence: 99%